QUALITY OF IMPLEMENTATION OF PUBLIC SERVICES IN THE PUBLIC SERVICE MALL (MPP) IN SUMEDANG DISTRICT - Ade Irawan (Lembaga Penelitian Universitas Pasundan, 2020)
This study is to examine Describe and analyze the quality of the implementation of public services by the district government in public services through the Public Service Mall (MPP) in Sumedang Regency. Seeing the supporting and inhibiting factors in the process of public service that refers to KememPan number 31 of 2019, there are still not many maximums from the start of regent regulations that have not yet come out, even though services have started to run, this study will analyze how public services should be carried out in the process of implementing public service systems through Public Service Mall (MPP) in Sumedang Regency. The method used in the activity is a descriptive method through a qualitative approach. With this method and approach, it is expected to be able to describe various problems in their entirety and comprehensively, so that the results of the problem analysis can be used as a basis for understanding phenomena and giving birth to a concept of the quality of public service delivery in Sumedang Regency.